Formation of chloronitrophenols upon sulfate radical-based oxidation of 2-chlorophenol in the presence of nitrite. (June 2020) - Zhao, Xulei; Zhang, Teng; Lu, Junhe; Zhou, Lei; Chovelon, Jean-Marc; Ji, Yuefei
Abstract: Sulfate radical (SO4 − )-based advanced oxidation processes (SR-AOPs) are promising in-situ chemical oxidation technologies widely applied for soil/groundwater remediation. The presence of non-target water constituents may interfere the abatement of contaminants by SR-AOPs as well as result in the formation of unintended byproducts. Herein, we reported the formation of toxic chloronitrophenols during thermally activated persulfate oxidation of 2-chlorophenol (2CP) in the presence of nitrite (NO2 − ). 2-Chloro-4-nitrophenol (2C4NP) and 2-chloro-6-nitrophenol (2C6NP) were identified as nitrated byproducts of 2CP with total yield up to 90%. The formation of nitrated byproducts is a result of coupling reaction between 2CP phenoxyl radical (ClPhO) and nitrogen dioxide radical (NO2 ). As a critical step, the formation of ClPhO was supported by density functional theory (DFT) computation. Both 2C4NP and 2C6NP could convert to 2-chloro-4, 6-dinitrophenol (2C46DNP) upon further treatment via a denitration-renitration process. The formation rate of 2C4NP and 2C6NP was closely dependent on the concentration of NO2 −, solution pH, and natural water constituents. ECOSAR calculation suggests that chloronitrophenols are generally more hydrophobic and ecotoxic than 2CP. Our result therefore reveals the potential risks in the abatement of chlorophenols by SR-AOP, particularly when high level of NO2 − is present in water matrix. Graphical abstract: Image 1 Highlights: SO4 − -induced incorporation of NO2 − nitrogen into 2-chlorophenol. Chloronitrophenols including 2C4NP, 2C6NP, and 2C46DNP were identified. NO2 and phenoxyl radical are responsible for the formation of chloronitrophenols. NO2 − and solution pH significantly affect the formation of chloronitrophenols. Formation of chloronitrophenols should be carefully scrutinized.